Chapter Fase di 'transizione critica' per il Sistema-Terra - Lombardi, Mauro (Studi e saggi, 2021)
Pandemic, health crisis, climate risk after decades of stressing natural capital because of overexploitation of resources and moreover increasing socio-economic inequalities are considered by many scholar to cause a tipping point in the evolution of bio-physical and socio-technical processes on a global level. In light of the systemic interdependencies of a hyper-connected world, the scenario of a global systemic crisis does not appear unlikely. We can try to avoid it by taking on new strategic priorities and mindset, then defining theoretical imperatives and application criteria. In this perspective, an example is the paradigm shift represented by the passage from the so-called shareholder capitalism to the stakeholder capitalism.